The role of non-profit organizations in territorial cohesion in cross-border regions - Potluka, O.; Schubnell, L.; Medeiros, E.; Weller, M. (Regional Science Policy and Practice, 2026)
Cross-border regions usually suffer from barriers hindering networking and creating contact among people. On a sample of 244 non-profit organizations (NPOs) in the Upper-Rhine region at the French, German, and Swiss borders, the research used partial least squares structural equation modeling (PLS-SEM) to investigate how NPOs contribute to social capital creation and cross-border territorial cohesion, via the reduction of persistent cross-border barriers. Results show that NPOs are similar to other types of stakeholders. They are primarily oriented at the local level, not towards cross-border cohesion. The primary networking and regional social capital creation are implemented throughout business activities. Barriers influencing cross-border territorial cohesion show that NPOs can effectively overcome them. For that, NPOs in all three countries in our sample follow similar values and principles of work.